English homework for key stage 2 [ activity-based learning - McGowan, Andrea; Forster, Colin , 1926-; Parfitt, Vicki (Active homework, 2010)
Suitable for busy teachers, this title presents a selection of 'pencil-free' activities, aligned with the National Curriculum Programmes of Study and with links to the topics set out in the PNS